Signaling by Gasotransmitters - Mustafa, Asif K. (2009)
Nitric oxide is well established as a major signaling molecule. Evidence is accumulating that carbon monoxide and hydrogen sulfide also are physiologic mediators in the cardiovascular, immune, and nervous systems. This Review focuses on mechanisms whereby they signal by binding to metal centers in metalloproteins, such as in guanylyl cyclase, or modifying sulfhydryl groups in protein targets.